Destination and essence of Arabic studies in Russia - Sumbel Usmanovna Sabitova, Mohammed Saleh Al-Ammari,; Al-Hannash, Mohammed (Opción, 2019)
The article describes the paths of development and the formation stages of Russian Arabic studies via the systematization of the accumulated body of knowledge about Russian Arabic studies, as well as the analysis of the information received and the synthesis of new ideas. As a result, after the changes in the world linguistic science, communicative competences came to the forefront in foreign language teaching, and grammar faded into the background. Thus, it can be concluded that Russian Arabic studies have great potential for development and rich history.